2017
DOI: 10.1038/bjc.2017.104
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of DNA methylation at chromosome 8q24 in peripheral blood and prostate cancer risk

Abstract: Background:Chromosome 8q24 has emerged as an important genetic susceptibility region for several cancers, including prostate cancer; however, little is known about the contribution of DNA methylation in this region to risk.Methods:We prospectively evaluated DNA methylation at 8q24 in relation to prostate cancer using pre-diagnostic blood samples from 694 prostate cancer cases (including 172 aggressive cases) and 703 controls in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. We used logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…1), is overexpressed in prostate tumor tissues. DNA methylation in MYC is associated with prostate cancer aggressiveness (16,17). The MYC oncogene works as a transcriptional activator that is involved in cell growth, apoptosis, and differentiation (8,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…1), is overexpressed in prostate tumor tissues. DNA methylation in MYC is associated with prostate cancer aggressiveness (16,17). The MYC oncogene works as a transcriptional activator that is involved in cell growth, apoptosis, and differentiation (8,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation changes can be monitored at repetitive elements (e.g., Alu and LINE‐1 ), and is used as surrogate measures of global methylation that is associated with cancer [Neale et al, ; Barry et al, ]. In this study, we examined the methylation status of Alu and LINE‐1 and its association with levels of urinary arsenic in 84 school‐age children living in two contaminated sites located in San Luis Potosí, where high concentrations of arsenic in surface soil and household dust have been found because of important mining activities in the past [Yáñez et al, ; Carrizales et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have already reported aberrant methylation of repetitive sequences in blood of patients with cancer. Barry et al 32 reported Alu hypermethylation in blood of patients with prostate cancer. Additionally, both hypomethylation and hypermethylation of LINE-1 CpGs were detected in the blood of patients with pancreatic, colon, and gastric cancer 33.…”
Section: Discussionmentioning
confidence: 99%